Food system resilience contributions by urban agriculture - Walker, Kara Elizabeth (My University, 2026)
Food systems face continued disruptions, including pandemics and severe weather events. Resilience is the ability of a system to respond and adapt to disruptions. The capacity of urban and peri-urban agriculture (UA) sites to provide resilience is an important part of nutritional security in cities. While research in this field is growing, there are gaps in understanding for resilience contributions from specific categories of UA sites. This thesis provides literature and research-based accounts of how urban agriculture can contribute to resilience. Chapter one provides a review of food system assessment instruments that are used in research. A PRISMA review was used to collect academic and nonacademic assessment tools for food system resilience and compare the intended audience; spatial scope; data type; data collection; strengths; and ease of use. The frameworks matched some but not all of the selected resilience attributes. Intended audience, data collection needs, and ease of use varied. Several limitations were identified, including burden of data collection and analysis, and lack of consideration for farm labor. Based on the results of the review, recommendations were made for diverse actors within the food system to select an appropriate assessment tool. Chapter two is a review of the literature that sought to identify specific resilience attributes with a narrative literature review, including situating the urban food system as a socioecological system with resilience capacities for responding to disruptions. We identified behavior-based indicators of social resilience, including civic engagement, political engagement, social capital, and transformational capacity, that were appropriate for UA site operators and participants. Chapter three comprises original research that is part of a four-pronged transdisciplinary assessment of urban food systems; other assessment areas include environmental sustainability, agricultural productivity, and community health. This study aimed to develop a survey instrument to assess and compare resilience capacities of six types of UA sites: urban production, periurban production, intensive production, community gardens, high school gardens, and training farms. Civic engagement, political engagement, social capital including trust and collaboration, and transformational capacity were selected to measure social resilience for participants and operators of UA sites. Methods including validated surveys and interview questions were developed with an advisory board of food system experts. Site operators and participants indicated they felt qualified to participate in the political process, tended to follow local politics, and felt they could have an impact on making their communities better places to live. Operators also had strong patterns of outreach and collaboration, diverse allies, and a multitude of motivating factors. The effect of site type was significant for participants and some types of political engagement, such as signing petitions and indicators of social capital, including trust. Community garden and intensive production site participants had strong indicators of social capital and political engagement significantly correlated with site type, and all site types had strong indicators of civic and political engagement and social capital. These data provide a picture of social resilience contributions by UA site type and underscore the need for planners and policymakers to develop appropriate supports for growing food in and around cities, regardless of the site type. The results could be used to inform UA policy for socially resilient communities.
Keywords: Urban agriculture; Urban food systems; Food system resilience; Social capital; Social resilience